Study of the effect of polyelectrolytes with antiviral effect on the activity of influenza virus neuraminidase and the process of oxidative phosphorylation in mitochondrias of cells host organism - N. A. Kontarov; I. V. Pogarskaya; N. V. Yuminova (Журнал микробиологии, эпидемиологии и иммунобиологии, 2019)
Aim. Study of the inhibitory effect of polyelectrolytes with antiviral effect against influenza neuraminidase. Determination of the type and inhibition constant. The study of the effect of polyelectrolytes (PE) on the process of oxidative phosphorylation in the mitochondria of cells host organism. Materials and methods. Purified influenza virus strains were used: A/VPCH/Weybridge (H7N7), A/Mallard Pennsylvania/10218/84 (H5N2), A/NIBRG-14 (H5N1) with an initial infectious titer of 4,5 lgTCD50/ml. PE solutions of polystyrenesulfonate with a degree of polymerization of 8 (PSS-8) in concentrations of 0,5—4,0 mM and polyallylamine (6 kDa) PAA (6 kDa) in concentrations of 0,5—4,0 μM. To determine the activity of influenza neuraminidase, influenza virus strains were used after the removal of low molecular weight inhibitors of neuraminidase by dialysis against water. The neuraminidase substrate was fetuin at final concentrations of 0,052 to 1,2 μM for PAA (6 kDa) and from 0,052 to 1,2 mM for PSS-8. As quantitative characteristics of respiration and phosphorylation of mitochondria, respiratory coefficients according to Lardi-Velman and Chans-Williams, as well as the ratio of ADP/O were used. Mitochondria were isolated from skeletal muscle. The determination of respiratory coefficients and the ratio of ADP/O) was determined by the polarographic method. Results. A noncompetitive type of inhibition of these PEs was detected in relation to the neuraminidase activity of influenza viruses with inhibition constants KI = 1,6 ± 0.08 μM for PAA (6 kDa) and KI = 1,7 ± 0.085 mM for PSS-8. Respiratory coefficients and the ratio of ADP / 0 were determined in the absence and after addition of PSS-8 and PAA (6 kDa) to mitochondria at concentrations of 20 mM and 10 μM, respectively. A decrease in respiratory coefficients and an ADP/O ratio was observed, indicating an inhibition of the enzymes of the electron-transport chain of mitochondria. At concentrations of less than 20 mM and 10 μM for PSS-8 and PAA (6 kDa), all indicators did not significantly change. Conclusion. The non-competitive mechanism of inhibition of the neuraminidase activity of the influenza PE viruses is explained by the conformational changes in the molecules of the enzyme and/or enzyme-substrate complex and, accordingly, the structural and functional changes in its secondary structure. When going beyond the range of non-toxic concentrations of20 mM for PSS-8 and 10 μM for PAA (6 kDa), inhibition of the mitochondrial respiratory chain enzymes was observed while maintaining the antiviral effect.